IDENTIFIKASI KEMAMPUAN SISWA KELAS V SD DALAM MERENCANAKAN PENYELIDIKAN ILMIAH MATERI SIKLUS AIR - Yosefin Aprilia; Rusmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Scientific literacy is a crucial competency that must be developed from the elementary school level, yet PISA results indicate that Indonesian students' scientific literacy remains relatively low, partly due to the limited scientific inquiry activities in science learning. This study aims to identify the level of fifth-grade elementary school students' abilities in planning scientific inquiry on water cycle material based on the PISA Framework 2025. This study employed a quantitative descriptive method with 55 fifth-grade students from SDN K in the 2025/2026 academic year selected through total sampling technique. Theresearch instrument consisted of 10 multiple-choice questions that had been validated and tested for reliability, with data analyzed using descriptive statistics. The results show that 59% of students have good abilities in planning scientific inquiry with an average score of 68.73, while 42% of students remain in the low and very low categories with a high standard deviation of 25.46, indicating significant ability variation among students. This study concludes that fifth-grade students at SDN K possess good ability levels in planning scientific inquiry competence; however, more intensive learning improvement effortsare needed for students in the low category to enhance scientific literacy comprehensively.